Microbial Communities of Polymetallic Deposits’ Acidic Ecosystems of Continental Climatic Zone With High Temperature Contrasts - Gavrilov, Sergey N.; Korzhenkov, Aleksei A.; Kublanov, Ilya V.; Bargiela, Rafael; Zamana, Leonid V.; Popova, Alexandra A.; Toshchakov, Stepan V.; Golyshin, Peter N.; Golyshina, Olga V. (Frontiers in Microbiology, 2019)
Acid mine drainage (AMD) systems are globally widespread and are an important source of metal pollution in riverine and coastal systems. Microbial AMD communities have been excessively studied for their ability to thrive under extremely acidic conditions and for their immense contribution to the dissolution of metal ores. However, little is known on microbial inhabitants of AMD systems subjected to extremely contrasting continental seasonal temperature patterns as opposed to maritime climate zones, experiencing much smaller annual temperature gradients. Here, we investigated three types of AMD sites in Eastern Transbaikalia. In this region, all surface water bodies undergo a deep and long (up to 6 months) freezing with seasonal temperatures varying between -33 to +24 ºC, which starkly contrasts the common well-studied AMD environments. We sampled acidic pit lake (site Sherlovaya Gora) located in the area of polymetallic deposit, acidic drainage water from Bugdaya gold-molybdenum-tungsten deposit and Ulan-Bulak natural acidic spring. These systems showed a predominance of bacteria mostly affiliated with Actinobacteria, Acidobacteria, Alpha- and Gammaproteobacteria, Cyanobacteria, Chloroflexi, Bacteroidetes and Firmicutes. Furthermore, candidate taxa 'Ca. Saccharibacteria' (previously known as TM7), 'Ca. Parcubacteria' (OD1) and WPS-2 were represented in substantial quantities. Heterotrophy and iron redox cycling can be considered as central processes of carbon and energy flow for majority of the detected bacterial taxa. Archaea were detected in low numbers, with TMEG (Terrestrial Miscellaneous Euryarchaeal group), to be most abundant (3%) in acidic spring Ulan-Bulak. Composition of these communities was found to be typical in comparison to other AMD sites; however, certain groups (as Ignavibacteria) could be specifically associated with this area. This study provides insight into the microbial diversity patterns in acidic ecosystems formed in areas of polymetallic deposits in extreme continental climate zone with contrasting temperature parameters and suggests high adaptability and biotechnological potential for these microorganisms.